Effect of particle size on nonlinear refraction and absorption of Ag nanoparticles - Shahriari, Esmaeil; Mat Yunus, Wan Mahmood (Institute of Materials Physics, 2010)
The nonlinear optical characteristics of silver nanofluid synthesized by γ-radiation technique at a concentration of 5.889×10-3M were studied. The measurements were performed by a single Z-scan method using CW laser beam excitation wavelength of λ= 532 nm. The nonlinear refractive index and the nonlinear absorption of samples were determined for nanoparticle sizes ranging from 40.8 to 64.1 nm. It is shown that the nonlinear refraction of the samples caused by the thermal effect increased nonlinearly with particle size. However, the nonlinear absorption coefficient rapidly decreases up to the particle size of 52 nm and tends to increase for particle size greater than 52 nm. The third order nonlinear susceptibility of all series of samples is also calculated and discussed.